Abramowitch, S A.(Architect) Pocardi Restaurant. Black and white photograph. - Abramowitch, S A (My University, 2012)
Abramowitch, S A.(Architect) Pocardi Restaurant. Black and white photograph.
Abramowitch, S A.(Architect) Pocardi Restaurant. Black and white photograph. 192X247.
Keywords: Abramowitch, S A.(Architect) Pocardi Restaurant. Black and white photograph.